The conceptualisation of morality in Judaism - Gavin Michal (Verbum et Ecclesia, 2024)
This article dealt with the irony that confronts any investigation into the conceptualisation of morality in Judaism: much of contemporary scholarship promotes the Strong Dependence Theory where God is considered the prime source of morality − yet an empirical analysis of classical rabbinic literature indicates a leaning more towards the Weak Dependence Theory which considers human beings the source for morality. Somehow, scholarship seems to overlook this textual evidence. On the other hand, that same contemporary scholarship has no problem in accepting absolute and complete human autonomy in the area of Jewish religious law or Halacha. This study questioned why humans are comfortably accepted as the primary determinants of religious law but not of morality – and argued for a return to the original Weak Dependence Theory to maintain moral efficacy. It included an examination of an extreme historical test case for rabbinic morality concerning how the rabbinic world dealt internally with the moral implications of major rabbis who had fled the Holocaust.